202 Targeted sequencing in 1200 SLE patients reveal DAP1 regulatory haplotype that potentiate autoimmunity. (April 2019) - Raj, Prithvi; Song, Ran; Riediger, Linley; Jun, Dong-Jae; Dozmorov, Igor; Liang, Chaoying; Zhang, Bo; Wakeland, Benjamin; Arana, Carlos; Zhou, Jinchun; Karp, David R; Li, Quan; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is characterized by the presence of autoantibodies and multi-system immune-mediated pathology. Genome-wide association studies have identified >60 SLE risk loci, suggesting a polygenic susceptibility. Although these loci account for significant genetic heritability, a large proportion is still missing. The missing heritability can be explained by the genetic component of intermediate phenotypes contributed by low frequency functional variants not captured on classical SNP arrays. Deep targeted sequencing of SLE associated genes allows comphensive and personalized assessment of genetic risk by annotating all common and rare disease causing variants. This study was performed to investigate functional variants in the gene for Death associated protein 1 (DAP1) that was previously implicated in susceptibility to SLE. Methods: We performed deep targeted sequencing of the DAP1 locus in 1221 SLE and 814 healthy control samples capturing both common and rare SLE associated variants. Genetic association analysis was carried out to identify disease associated haplotypes. SLE associated variants were annotated for functional efffects using publically available resources and an eQTL panel of healthy donors. Serum autoantibody signatures and gene expression profiles of SLE patients carrying SLE risk or protective geneotypes were analyzed in combination with the level of DAP1 transcription and translation. Since DAP1 protein is a potent negative regulator of autophagy, the effect of its downregulation in the risk group, was assessed in a functional autophagy assay. Results: Sequencing of the DAP1 gene revealed a novel, functional haplotype that poses risk [OR=1.5, p=4.5E-05] for SLE. The association was replicated in two independent cohorts of patients from different ethnic groups. RNA sequencing analysis revealed multiple cis-eQTLs embedded in the risk haplotype that downregulate DAP1 expression in immune cells. Decreased DAP1 transcription in the risk allele was consistent with reduced protein level. Healthy donors with the DAP1 risk genotype had a significantly elevated ratio of LC3-II/LC3-I in PBMCs and monocytes under starvation, suggesting enhanced autophagy mediated by the risk haplotype. SLEs with the risk genotype exhibhited significantly high autoantibody titers and altered expression of autophagy and apoptosis pathway molecules. Conclusions: This study reports a regulatory haplotype in the DAP1 locus associated with a reduced DAP1 protein level and enhanced autophagy in immune cells that can promote survival of autoreactive lymphocytes and potentiate autoimmunity. Funding Source(s): Alliance for lupus research, NIH, UTSW Panel a: shows the sequencing depth across DAP1 gene locus on chromosome 5. Panel b: shows the 62 kb LD (Linkage Disequilibrium) block that contain top 19 SLE associated variants (rsIds shown). The peak SLE associated SNP rs267985 and strongest DAP1 eQTL rs2930047 are shown. Panel c: Median-joining (MJ) network analysis on most common DAP1 haplotypes in Caucasian SLEs and healthy controls. Spheres (termed nodes) represent the locations of each haplotype (from table 2) within the network and the size of the node is proportional to the overall frequency of that haplotype in the dataset. Each node is overlaid with a pie chart that reflects the frequency of that haplotype in SLE group (yellow) versus healthy group (black). The lines connecting the nodes are labeled with the variants that distinguish the connected nodes and the length is proportional to the number of variants. Odds ratio (OR) are shown for two most significant alleles. Red highlighted nodes indicate SLE risk clades.. Panel d: Median-joining (MJ) network analysis on most common DAP1 haplotypes in African American SLEs and healthy controls.. Panel e: Median-joining (MJ) network analysis on most common DAP1 haplotypes in Asian SLEs and healthy controls.